Kampanye Lingkungan Bersih dan Bebas Sampah Plastik di Wilayah Grobogan - Dzakia Esa Kusuma Putri; Nasywaa Fauziyyah Mumtaz; Nilam Listianingrum; Naura Athaya Anindita; Andira Nur Fattah (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
Cleanliness plays an integral and crucial role in human existence. Maintaining a clean environment signifies the creation of a wholesome setting, free from pollutants such as dust, waste, and unpleasant smells. As per the World Health Organization (WHO), environmental health relies on achieving an ecological equilibrium between humans and their surroundings to ensure human well-being. A hygienic environment serves as a protective shield against various diseases like dengue fever, malaria, and gastrointestinal illnesses. The impact of environmental cleanliness extends beyond health, influencing the overall comfort, aesthetics, and tranquility of an area. Promoting cleanliness involves simple yet impactful actions, beginning with the upkeep of the immediate surroundings. Initiatives are required to instill a sense of responsibility among the community for their environment. In delivering community service, various methods such as discussion, education, and practical field activities are employed. Upon completion of these activities, it was evident that the residents of Malasom Village have, to some extent, overlooked the cleanliness of their surroundings. Consequently, collaborative efforts from multiple stakeholders are necessary to foster awareness and commitment towards maintaining the cleanliness and health of their living environment.